Household air pollution and its effects on health [version 1; referees: 2 approved] - Komalkirti Apte; Sundeep Salvi (F1000Research, 2016)
Household air pollution is a leading cause of disability-adjusted life years in Southeast Asia and the third leading cause of disability-adjusted life years globally. There are at least sixty sources of household air pollution, and these vary from country to country. Indoor tobacco smoking, construction material used in building houses, fuel used for cooking, heating and lighting, use of incense and various forms of mosquito repellents, use of pesticides and chemicals used for cleaning at home, and use of artificial fragrances are some of the various sources that contribute to household air pollution. Household air pollution affects all stages of life with multi-systemic health effects, and its effects are evident right from pre-conception to old age. In utero exposure to household air pollutants has been shown to have health effects which resonate over the entire lifetime. Exposures to indoor air pollutants in early childhood also tend to have repercussions throughout life. The respiratory system bears the maximum brunt, but effects on the cardiovascular system, endocrine system, and nervous system are largely underplayed. Household air pollutants have also been implicated in the development of various types of cancers. Identifying household air pollutants and their health implications helps us prepare for various health-related issues. However, the real challenge is adopting changes to reduce the health effects of household air pollution and designing innovative interventions to minimize the risk of further exposure. This review is an attempt to understand the various sources of household air pollution, the effects on health, and strategies to deal with this emergent risk factor of global mortality and morbidity.